Avaliação “in vitro” do efeito antitumoral e antiangiogênico de uma metaloprotease isolada da peçonha de Bothrops pauloensis - Guimarães, Denise de Oliveira (2016)
Breast cancer is a highly malignant carcinoma and remains the second leading cause of mortality among women. The antitumor effects of metalloproteinases and disintegrins from snake venom on various types of cancer cells have been investigated. In this study, we evaluated the antitumor and antiangiogenic effects on MDA-MB-231 human breast cancer cells and endothelial cells induced by Bothropoidin, a disintegrin-like metalloproteinase isolated from Bothrops pauloensis snake venom. At 24h after treatment at 100pg/mL, Bothropoidin exerted a moderate cytotoxic effect of 30% on MDA-MB-231 versus 10% cytotoxicity against MCF10A (a non-tumorigenic breast cell line), a significant difference that suggests a possible preference by this protein for targets in cancer cells. Early and late apoptosis of MDA-MB-231 was observed after Bothropoidin treatment (10gg/mL and 40gg/mL). Furthermore, this toxin inhibited not only the adhesion of MDA-MB-231 cells in a dose-dependent manner but also cell migration by approximately 45%. In addition, Bothropoidin decreased endothelial cells viability and adhesion in Matrigel and inhibited in vitro angiogenesis in Matrigel stimulated by bFGF, showing significantly fewer formed vessels. The results demonstrated that Bothropoidin has potent in vitro antitumor and antiangiogenic effect and represents a biotechnological tool for elucidating the antitumor effect of disintegrins-like metalloproteinases in cancer cells.